Analyzing Street Art to Present the Heritage of George Town, Malaysia - Sadatiseyedmahalleh, Seyedehelham; Rahman, Suraiyati; Abdullah, Aldrin (International Journal of Multicultural and Multireligious Understanding, 2015)
Street art comprises all kinds of art developed in public locations. This form of art has spread to all heritage streets in George Town, the capital of Penang Island, which is also a known UNESCO World Heritage Site. However, instead of its heritage, food, and interesting past life and structure, the rapid multiplication of street art in George Town has created a new and unusual art that attracts tourists. Street art has spread to small roads and heritage streets in the city. This art increases the awareness of spectators by introducing them to the rich history of these streets and inducing a lively concept in the inner city of George Town. Accordingly, the impact of iron rod sculptures and murals, which comprises approximately 90% of street art in George Town, were determined to explore and identify the effects of this street art on this world heritage site. The findings were obtained from 263 out of 306 questionnaires accomplished by tourists in George Town. The results confirm that tourists prefer murals over iron rod sculptures. Iron rod sculptures are designed to tell the history of the street, whereas murals are designed to create aesthetic value. The findings indicated that similar to iron rod sculptures, more control should be exercised on the subjects of murals.